2006
DOI: 10.1097/01.ccm.0000196829.30741.d4
|View full text |Cite
|
Sign up to set email alerts
|

Parenterally administered dipeptide alanyl-glutamine prevents worsening of insulin sensitivity in multiple-trauma patients

Abstract: Parenteral supplementation of alanyl-glutamine dipeptide was associated with better insulin sensitivity in multiple-trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(59 citation statements)
references
References 44 publications
(30 reference statements)
2
50
0
7
Order By: Relevance
“…This difference in glycemia levels could be due to the ability of glutamine to reduce insulin resistance in critically ill patients. This has also been recently confirmed by Bakalar et al 18 in an isotope study with hyperinsulinemic euglycemic clamp in severe trauma patients.…”
Section: Discussionsupporting
confidence: 67%
“…This difference in glycemia levels could be due to the ability of glutamine to reduce insulin resistance in critically ill patients. This has also been recently confirmed by Bakalar et al 18 in an isotope study with hyperinsulinemic euglycemic clamp in severe trauma patients.…”
Section: Discussionsupporting
confidence: 67%
“…Despite this difference being statistically significant, we believe that this should not be clinically significant. Slightly lower insulin consumption in group 2 in comparison with group 3 could be explained by the effects of alanylglutamine on insulin sensitivity [21]. Whether different insulin doses might influence the IGF-I-IGFBP axis is not clear, as previous studies gave conflicting results [22,23].…”
Section: Discussionmentioning
confidence: 97%
“…The effect of parenteral alanyl-glutamine on insulin resistance was investigated by Bakalar et al [ 70 ], who showed signifi cantly improved insulin sensitivity and insulin-mediated glucose disposal in the glutamine-supplemented patients. The rate of protein breakdown was not different between groups during the study, but hypermetabolism was attenuated in the glutamine group by reducing energy expenditure.…”
Section: Nitrogen Balance Protein Synthesis and Other Biochemical Oumentioning
confidence: 99%